The Long and Winding Road: A Systematic Literature Review Conceptualising Pathways for Hypertension Care and Control in Low- and Middle-Income Countries - Rachel Brathwaite; Eleanor Hutchinson; Martin McKee; Benjamin Palafox; Dina Balabanova (Kerman University of Medical Sciences, 2022)
BackgroundHypertension control is poor everywhere, especially in low- and middle-income countries (LMICs). An effective response requires understanding factors acting at each stage on the patients' pathway through the health system from entry or first contact with the health system, through to treatment initiation and follow up. This systematic review aimed to identify barriers to and facilitators of hypertension control along this pathway and, respectively, ways to overcome or strengthen them.MethodsMEDLINE, EMBASE, Global Health, CINAHL Plus, and Africa-Wide Information (1980-April 2019) were searched for studies of hypertensive adults in LMICs reporting details of at least 2 adequately described health system contacts. Data were extracted and analysed by 2 reviewers. Themes were developed using NVivo in patient-related (sociodemographic, knowledge and health beliefs, health status and co-morbidities, trade-offs), social (social relationships and traditions) and health system domains (resources and processes). Results are reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.ResultsFrom 2584 identified records, 30 were included in the narrative synthesis. At entry, 'health systems resources and processes' and 'knowledge and beliefs about hypertension' dominated while 'social relations and traditions' and 'comorbidities' assume greater importance subsequently, with patients making 'trade-offs' with family priorities during follow up. Socio-demographic factors play a role, but to a lesser extent than other factors. Context matters.ConclusionUnderstanding the changing barriers to hypertension control along the patient journey is necessary to develop a comprehensive and efficient response to this persisting problem.